Combustion of Al-Al2O3 mixtures in air; Journal of the European Ceramic Society; Vol. 25, iss. 9 - Gromov A. A. Aleksandr Aleksandrovich; Ilyin A. P. Aleksandr Petrovich; Ditts A. A. Aleksander Andreevich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich (2005, 2005)
Title screen